New analogs of the CART peptide with anorexigenic potency: the importance of individual disulfide bridges - Blechová, Miroslava; Nagelová, Veronika; Záková, Lenka; Demianová, Zuzana; Zelezná, Blanka; Maletínská, Lenka (Peptides, 2013)
The CART (cocaine- and amphetamine-regulated transcript) peptide is an anorexigenic neuropeptide that acts in the hypothalamus. The receptor and the mechanism of action of this peptide are still unknown. In our previous study, we showed that the CART peptide binds specifically to PC12 rat pheochromocytoma cells in both the native and differentiated into neuronal phenotype. Two biologically active forms, CART(55-102) and CART(61-102), with equal biological activity, contain three disulfide bridges. To clarify the importance of each of these disulfide bridges in maintaining the biological activity of CART(61-102), an Ala scan at particular S-S bridges forming cysteines was performed, and analogs with only one or two disulfide bridges were synthesized. In this study, a stabilized CART(61-102) analog with norleucine instead of methionine at position 67 was also prepared and was found to bind to PC12 cells with an anorexigenic potency similar to that of CART(61-102). The binding study revealed that out of all analogs tested, [Ala(68,86)]CART(61-102), which contains two disulfide bridges (positions 74-94 and 88-101), preserved a high affinity to both native PC12 cells and those that had been differentiated into neurons. In food intake and behavioral tests with mice after intracerebroventricular administration, this analog showed strong and long-lasting anorexigenic potency. Therefore, the disulfide bridge between cysteines 68 and 86 in CART(61-102) can be omitted without a loss of biological activity, but the preservation of two other disulfide bridges and the full-length peptide are essential for biological activity.
Keywords: Appetite Depressants; proteiny nervové tkáně; PC12 Cells; přijímání potravy; lokomoce; Eating; Nerve Tissue Proteins; nocicepce; buňky PC12; krysa rodu Rattus; zvířata; myši; Cystine; myši inbrední C57BL; Mice; Peptide Fragments; cystin; anorektika; Male; kompetitivní vazba; Mice, Inbred C57BL; Binding, Competitive; peptidové fragmenty; Rats; Nociception; Locomotion; Animals; mužské pohlaví